Exploring the Impact of Annual Report Inquiries on Audit Risk: Based on the Perspective of Anchoring Effect (Asian Business Research, 2023)
The assessment of material misstatement risk is a critical judgmental matter for CPAs, but the uncertainty and subjectivity of judgment lead to a qualitative description of risk evaluation. By sorting out the inquiry letters issued by stock exchanges to listed companies in recent years, constructing a material misstatement risk system using fault trees and quantifying them using fuzzy hierarchical synthesis analysis, this paper not only provides a new reference basis and new audit ideas for annual audits, but also helps CPAs to better identify and evaluate material misstatement risks and improve the effectiveness of audits during annual audits.